Endophthalmitis diagnosis supported by bedside ultrasound. Issue 5 (10th September 2022) - Gong, Jing Jing; Perkins, William; Frenkel, Jerry; Greco, Jeff; Desmond‐Combs, Kallie
Abstract: Endophthalmitis is a bacterial or fungal infection in the deep spaces of the eye. The diagnosis of endophthalmitis has traditionally been made by vitreous humor culture and is commonly missed on initial presentation. In this case report, we emphasize the role of ocular point‐of‐care ultrasound (POCUS) in revealing endophthalmitis as a primary differential diagnosis for a patient presenting with unilateral eye pain and significant swelling that limited physical examination of the eye. Here, the patient's initial clinical examination was more suggestive of an alternative diagnosis, orbital cellulitis, which could have delayed the highly morbid and time‐sensitive diagnosis of endophthalmitis. Although POCUS is traditionally enlisted for other posterior ophthalmic pathologies, including retinal detachment, vitreous detachment, vitreous hemorrhage, and papilledema, this rare case of endophthalmitis secondary to hepatic abscess demonstrates the utility of bedside ocular ultrasound as a tool to distinguish endophthalmitis from mimicking differentials when physical examination is unable to do so.